A New Research of Detection Device for Smart Wearable Equipment Step Counting Function. (May 2020) - Li, Peipei; Zhao, Yi; Yang, Yanfeng; Liu, Yong; Hu, Jianyu
Abstract: This article analyzes the current research status of smart wearable devices, proposes a step detection method for the smart wearable device, completes the hardware design and software programming of the device, and develops a test device for step counting function of smart wearable equipment. By testing the relevant products and collecting data, the relevant test results are given. The development of this device provides professional and credible testing data and results to the vast number of consumers and the general public. It can promote the innovation and development of the smart wear industry and deep integration with other industries and technologies. It also has great significance for testing institutions and enterprises.